Experimental evolution of aerobic exercise performance and hematological traits in bank voles - Lipowska, Małgorzata M.; Dheyongera, Geoffrey; Sadowska, Edyta T.; Koteja, Paweł (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2019)
The maximum rate of aerobic exercise metabolism (VO2max) is a trait informative from both medical and evolutionary perspective, and both the physiological mechanisms limiting its level and its evolution are subject to vivid debate. Both comparative analyses and studies on the effects of training or acclimation to aerobically-demanding conditions suggest a role of oxygen transport-related properties of blood in limiting VO2max. Here we used a unique experimental evolution model – lines of bank voles selected for high rate of swim-induced aerobic metabolism (VO2swim; A lines), which evolved a 60% higher VO2swim than that observed in unselected control lines (C) – and asked how the hematological parameters evolved in response to the selection. Voles from the A lines had a decreased hemoglobin concentration in cardiac blood samples (adjusted means ± SE, A: 14.7 ± 1.1, C: 15.3 ± 1.1 g/dl; p = .008), hematocrit (A: 51.7 ± 4.5, C: 53.8 ± 4.2%; p = .042) and tended to have less erythrocytes per microliter of blood (A: 11.5 ± 1.4, C: 12.7 ± 1.3 mln/μl; p = .083). The effect of selection was more pronounced in males than in females. Thus, selection for high aerobic-exercise performance resulted in a paradoxical decrease in traits positively associated with oxygen-carrying capacity per unit of blood volume, and the effect was sex-dependent. However, as a decreased blood viscosity associated with the lowered hematocrit reduces the costs of blood circulation, it can be hypothesized that the change can actually boost the oxygen supply to peripheral tissues. •The artificial selection resulted in a 60% increase of aerobic exercise metabolism.•The correlated response in hematological parameters was sex-specific.•Hematocrit and hemoglobin concentration decreased in males from the selected lines.